Sistemas fotovoltaicos aplicados em cenário de rede 5G - OLIVEIRA, Carmela Souza (Universidade Federal do Pará, 2025)
With the deployment of the next generation of mobile networks, a significant increase in data consumption is estimated and, consequently, a substantial impact on energy consumption. In light of this scenario, it is interesting to think of alternative sources that can meet this energy demand and additionally act to mitigate greater environmental impacts. Based on this economic and, above all, environmental perspective, this work proposes the use of a photovoltaic system as a strategy for the potentialization of energy consumption in a less aggressive way to the environment. The experiments carried out evaluate the viability of the proposal from the implementation in two RAN (Radio Access Network) architectures that can be employed to the new generation (5G). The results demonstrate the financial viability in the installation of photovoltaic system when compared to conventional sources of power generation.